The Influence of Renewable Energy, Carbon Emissions, and Foreign Direct Investment on Indonesia's Economic Growth 2011 - 2020 - Cyrill Ghauzan, Muhamad; Akbar Rizalihadi, Firman; Yulaikhah, Safitri; Ayunni, Tyarida; Annaty, Musahal (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This research aims to analyze the influence of the Green Economy concept on Indonesia's economic growth for the 2011-2020 period, focusing on three main pillars: environmental, social, and economic.     Design/Method/Approach : This research uses a quantitative approach with an associative design, analyzing secondary time series data from 2011 to 2020. Multiple linear regression analysis was used to examine the effect of carbon emissions (CO₂), renewable energy consumption, and Foreign Direct Investment (FDI) on economic growth as measured by Gross Domestic Product (GDP).          Research Finding : The results of the study show that simultaneously, carbon emissions, renewable energy, and FDI have a significant influence on Indonesia's economic growth. However, partially these three variables did not show a significant effect. Dependence on fossil energy (carbon emissions) still contributes to economic growth, while the transition to renewable energy and an increase in FDI have not had a significant impact on the period. Theoretical contribution/Originality : This research contributes to understanding the complexity of the relationship between Green Economy indicators and economic growth in developing countries such as Indonesia, particularly highlighting the challenges of energy transition and the role of foreign investment in the context of sustainability. Practical/Policy implication : This research implies the need for more comprehensive and long-term policies to integrate Green Economy principles in Indonesia's economic development strategy. Efforts are needed to accelerate the renewable energy transition and ensure foreign investment supports sustainable development. Research limitation : This research is limited to the 2011-2020 time period and only considers three independent variables. Other factors affecting economic growth and long-term policy dynamics are not covered.